Computer Speech-Based Remediation for Reading Disabilities: The Size of Spelling-to-Sound Unit in a Transparent Orthography - Jiménez, Juan E.; Hernández Valle, Isabel; Ramírez, Gustavo; Ortiz, Mª Del Rosario; Rodrigo, Mercedes; Estévez, Adelina; O’shanahan, Isabel; García, Eduardo; Trabaue, María De La Luz (The Spanish Journal of Psychology, 2007)
This study was designed to assess the effects of four reading-training procedures for children with reading disabilities (RD) in a transparent orthography, with the aim of examining the effects of different spelling-to-sound units in computer speech-based reading. We selected a sample of 83 Spanish children aged between 7 years 1 month and 10 years 6 months (M = 105.2, SD = 7.8) whose pseudoword reading performance was below the 25th percentile and IQ > 90. The participants were randomly assigned to five groups: (a) the whole-word training group (WW) (n = 17), (b) the syllable training group (S)(n = 16), (c) the onset-rime training group (OR) (n = 17), (d) the phoneme training group (P) (n = 15), and (e) the untrained control group (n = 18). Children were pre- and post-tested in word recognition, reading comprehension, phonological awareness, and orthographic and phonological tasks. The results indicate that experimental groups who participated in the phoneme and syllable conditions improved their word recognition in comparison with thecontrol group. In addition, dyslexics who participated in the phoneme, syllable, and onset-rime conditions made a greater number of requests during computer-based word reading under conditions that required extensive phonological computation (low frequency words and long words). Reading time, however, was greater for long words in the phoneme group during computer-based reading. These results suggest the importance of training phonological processes in improving word decoding in children with dyslexia who learn in a consistent orthography.